2004
DOI: 10.1097/01.asn.0000115401.07980.0c
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and Size of IgA1 Are Essential for Interaction with Mesangial Transferrin Receptor in IgA Nephropathy

Abstract: Transferrin receptor (TfR) has been identified as a candidate IgA1 receptor expressed on human mesangial cells (HMC). TfR binds IgA1 but not IgA2, co-localizes with mesangial IgA1 deposits, and is overexpressed in patients with IgA nephropathy (IgAN). Here, structural requirements of IgA1 for its interaction with mesangial TfR were analyzed. Polymeric but not monomeric IgA1 interacted with TfR on cultured HMC and mediates internalization. IgA1 binding was significantly inhibited (>50%) by soluble forms of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 47 publications
4
134
0
1
Order By: Relevance
“…These complexes stimulate cultured human mesangial cells (3)(4)(5), resulting in activation of oxidative stress pathways (6 -8). Evidence of increased oxidative stress has been noted in renal tissue of patients with IgAN (9) as well as in their sera and/or erythrocytes (i.e., increased levels of lipoperoxide or malondialdehyde and reduced activity of superoxide dismutase, catalase, and glutathione peroxidase) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…These complexes stimulate cultured human mesangial cells (3)(4)(5), resulting in activation of oxidative stress pathways (6 -8). Evidence of increased oxidative stress has been noted in renal tissue of patients with IgAN (9) as well as in their sera and/or erythrocytes (i.e., increased levels of lipoperoxide or malondialdehyde and reduced activity of superoxide dismutase, catalase, and glutathione peroxidase) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…60 IgA size seems to play a significant role in the pathogenicity of the IgA IC. Indeed, polymeric but not monomeric IgA1 induces TfR hyperexpression on human mesangial cells, 61 leading to increased production of cytokines (IL-6, transforming growth factor-b and tumor necrosis factor-a), mesangial expansion and pIgA1 mesangial deposition. 62,63 Studies employing lectins, which bind to glycosidic residues, revealed that circulating and mesangial IgA1 molecules from IgAN patients possess truncated O-glycans.…”
Section: Iga Dysfunction and Inflammatory Diseases C Papista Et Al 128mentioning
confidence: 99%
“…Our group has also shown that aberrant glycosylation of IgA1 and IC formation constitute essential factors favoring mesangial IgA1-TfR interactions as initial steps in IgAN pathogenesis. 61 The formation of the circulating IC may involve at least three distinct mechanisms: the self-aggregation of aberrantly glycosylated IgA1; the formation of complexes with soluble FcaRI; and the induced aggregation by interaction of IgA1 with other circulating proteins. As discussed above, the first mechanism is directly linked to the abnormal structure of IgA1.…”
Section: Iga Dysfunction and Inflammatory Diseases C Papista Et Al 129mentioning
confidence: 99%
“…IgAN injury [86] . Finally, as an alternative hypothesis, has been proposed that the soluble form of the Fcα receptor (sCD89) might "per se" generate complexes with GdIgA1 [87] .…”
Section: Salvadori M Et Al Pathophysiology Of Nephropathymentioning
confidence: 99%
“…Indeed, the mesangial cells binding to IgA-IC containing poorly galactosylated IgA1 triggers the proliferation and the programmed death of the mesangial cells. In addition a reduced synthesis of vascular endothelial growth factor (VEGF), an abnormal integrin production and an abnormal production of extracellular matrix increase the renal damage [86,[90][91][92] . The role of complement in the activation of the mesangial cells in IgAN has been recently reviewed by Maillard et al [93] .…”
Section: Step 4: Mesangial and Glomerular Cells Activation Glomerulamentioning
confidence: 99%